Jedan tip imeničkih složenica u kajkavskome književnom jeziku - Štebih Golub, Barbara (Slavia Centralis, 2020)
One Type of Noun Compound in the Kajkavian Literary Language The topic of this paper is the description of a type of nominal compound in the Kajkavian literary language – the standardized idiom that had performed the function of standard language in North-West Croatia in the period between the sixteenth century and the 1830s and the formation of the Croatian Standard language constructed on the basis of the Štokavian dialect. From the published volumes of the Dictionary of Kajkavian Literary Language (Rječnik kajkavskoga književnoga jezika), and the card files of the Institute of Croatian Language and Linguistics, a corpus was excerpted containing around 300 nominal compound words whose first root morpheme is a noun and the second root morpheme is a verb and which were formed by means of blending and suffixation. This paper analyzes their structure and presents an alphabetical list of productive suffixes in the word-formation processes. Since composition is considered to be a rare word formation process in the Slavic languages, this paper discusses the reasons for such a large number of compound words in the Kajkavian literary language. The analysis is based on the sources in which the compound words are found, as well as their attestation, with a goal of determining whether they are hapax legomena of single authors or lexicographers. It is also noted that there is a possibility that the incentive for the creation of a large number of compound words came from calques from Latin and German models.